How could future professionals excel in wine tourism delivery? Evidence from wine regions in emerging economies - Duarte Alonso, Abel; Kok, Seng Kiat (Emerald, 2020)
Purpose – The purpose of this study is to investigate the different traits, characteristics, and skills future professionals need to contemplate in order to address the demands of the competitive wine industry, more specifically, concerning the provision of wine tourism experiences. The insights within self-determination theory are considered to develop more robust understanding of this central theme.